Intelligent Computing Proceedings of the 2018 Computing Conference, Volume 1 - Arai, Kohei; Kapoor, Supriya; Bhatia, Rahul; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book, gathering the Proceedings of the 2018 Computing Conference, offers a remarkable collection of chapters covering a wide range of topics in intelligent systems, computing and their real-world applications. The Conference attracted a total of 568 submissions from pioneering researchers, scientists, industrial engineers, and students from all around the world. These submissions underwent a double-blind peer review process. Of those 568 submissions, 192 submissions (including 14 poster papers) were selected for inclusion in these proceedings. Despite computer science's comparatively brief history as a formal academic discipline, it has made a number of fundamental contributions to science and society-in fact, along with electronics, it is a founding science of the current epoch of human history ('the Information Age') and a main driver of the Information Revolution. The goal of this conference is to provide a platform for researchers topresent fundamental contributions, and to be a premier venue for academic and industry practitioners to share new ideas and development experiences. This book collects state of the art chapters on all aspects of Computer Science, from classical to intelligent. It covers both the theory and applications of the latest computer technologies and methodologies. Providing the state of the art in intelligent methods and techniques for solving real-world problems, along with a vision of future research, the book will be interesting and valuable for a broad readership.
Dynamic Control of Explore/Exploit Trade-Off in Bayesian Optimization -- A Bayesian Approach for Analyzing the Dynamic Relationship between Quarterly and Monthly Economic Indicators -- Sentiment Analysis System for Roman Urdu -- User Centric Mobile based Decision-Making System using Natural Language Processing (NLP) and Aspect based Opinion Mining (ABOM) Techniques for Restaurant Selection -- Optimal Moore Neighborhood Approach of Cellular Automaton based Pedestrian Movement: A Case Study on the Closed Area -- Biometric Image Enhancement, Feature Extraction and Recognition Comprising FFT and Gabor Filtering -- Gramatical Facial Expression Recognition with Artificial Intelligence Tools -- Intelligent Health Monitoring using Smart Meters -- Detecting Situations from Heterogeneous Internet of Things Data in Smart City Context -- A Secure Key Management Technique through Distributed Middleware for the Internet of Things -- On Programming Models, Smart Middleware, Security and Self-Healing for the Next-Generation Internet-of-Things -- Revisiting Industry 4.0: A New Definition.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence